Perancangan Sistem Informasi Penerimaan Peserta Didik Baru (PPDB) Pada Tingkat MTs - Supriyanto; Basiroh; Rifqi Fauzi Rahmadzani (Program Studi Teknik Informatika Universitas Nusa Putra, 2024)
The design of the MTs New Student Admission Information System is currently still carried out manually in the process of accepting prospective new students and creating reports on new student acceptance activities. The aim of this research is to design an MTs New Student Admission Information System that can assist the committee in the process of accepting prospective new students and producing reports on new student acceptance activities. The research methodology directly uses direct observation and interviews and uses literature documents. Materials and research material in the form of information on registrant data, charter data, and PPDB selection data. This system consists of several elements, namely master data, PPDB data, reports, tools, and help which are created and processed with Microsoft Visual Foxpro 9.0, with storage and results research in the form of an MTs New Student Admission Information System. With this system, it can be used as an alternative in order to simplify the process of accepting prospective new students and preparing reports on activities for accepting new students quickly, easily and accurately..